Improving Wind Turbine Performance by Intelligent Pitch Angle Control - Zeinab Hammoud; Salah Dawod; Fadi Motawej (Latakia University Journal -Engineering Sciences Series, 2024)
This paper presents an effective control strategy for wind turbine that it ensure the continuity of its work and its benefits by producing energy and maintaining the life of the turbine despite the changing wind speed and its turbulence. This paper discusses pitch angle control at high wind speed to reduce the corresponding loads on the turbine and preserve its parts. Yaw angle control at low wind speed to get the maximum power out of the turbine. Artificial intelligence techniques have been used (neural networks and fuzzy logic) to design a controller capable of adapting to changing wind conditions. Neural network and fuzzy logic work effectively when the nature of the system is variable and non-linear. The proposed controller was compared with pid and fuzzy pid controllers, and the results showed that the proposed controller achieved better results in term of response speed and reduce steady-state error.